Entre o sertão e o mar: o Projeto de Cultura Nacional de Leonardo Mota - Holanda, Juliana Tália Ribeiro de (2014)
In the first decades of the twentieth century, Brazilian intellectuals discussed relations between the Brazilian hinterlands and coastal cities. One was Leonardo Mota (1891- 1948) that examined these relationships by calling attention to the "divorce between the Interior and the Sea" (MOTA, 1925, p.5). However, this "divorce" and difficult relationship between the hinterland and the Brazilian coast were not new, brought the unfolding of a series of constructs images and ideas produced historically. This paper makes an analysis about the construction of the national culture project created by Leonardo Mota in the years 1920-1930 and the historicity of the constructions of these images and ideas that influenced the consolidation of the distance between the hinterland and the coast, and also contributed in formation of national identities.